Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Carbon emission prediction based on spatial–temporal pattern recognition and novel integrated vine copula - A. Xu; S. Fang; J. Chen; Z. Fu; Z. Chen (International Journal of Environmental Science and Technology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Metallogenic age and geological significance of the Jiazishan Mo deposit, Inner Mongolia, China - Z. L. Wang; J. Z. Yang; K. Q. Zhao; Y. G. Fu; J. W. Gao; Y. M. Deng; L. J. Lin; Z. Duan (Australian Journal of Earth Sciences, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Performance and mechanism of NiO/La-KTaO3 composite photocatalysts for UV degradation of isoamyl xanthate in synthetic flotation wastewater - X. Xu; L. Zhu; C. Chen; C. Luo; Z. Jin; Z. Sun; Z.T Fu (International Journal of Environmental Science and Technology, 2025)

Constraints of the paleowind directions on the paleogeography of the North China, South China and Tarim cratons during the Ediacaran Period - C. L. Hu; Z. Q. Lin; J. A. Quaye; X. B. Fu (Australian Journal of Earth Sciences, 2025)

Increasing humification and reducing CH4 emission during rice straw fermentation: the role of Streptomyces rochei ZY-2 - B. Fu; B. Gao; J. Zhang; H. Huang; Z. Wei; Q. Wang; P. Qu (International Journal of Environmental Science and Technology, 2025)

Ammonia inhibition in anaerobic digestion of organic waste: a review - J. Yang; J. Zhang; X. Du; T. Gao; Z. Cheng; W. Fu; S. Wang (International Journal of Environmental Science and Technology, 2025)
Anaerobic digestion (AD) has become the technology of choice for organic waste treatment as an environmentally beneficial and sustainable waste treatment technology. However, the nitrogen content of these organic waste streams is generally high. Ammonia is produced in the biodegradation of nitrogenous organic matter. Low concentrations of ammonia favour AD, but high concentrations can lead to digestive system failure. To address the issue of ammonia inhibition and ensure the stability of the digestive system, numerous physical, chemical, and biologicalmethods aimed at controlling ammonia levels and/or strengthening the biological processes have been proposedand developed. Literature evidence suggests that differences in AD reaction conditions and microbial sources result in different tolerances of the digestive system to ammonia and nitrogen. This paper summarises and compares the inhibitory effects of ammonia nitrogen under different conditions and the existing regulatory measures to alleviate ammonia nitrogen inhibition. In addition, since the core of the digestive system is microorganisms, this paper explains the mechanism of ammonia stress especially at the microbial level, and in this way, it explores the future direction of research using biofortification. This review provides a theoretical reference for solving the problem of ammonia nitrogen inhibition.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

R&D investment and corporate total factor productivity under the heterogeneous environmental regulations: evidence from Chinese micro firms - X. Ding; Y. Zhang; Y. Fu; Z. Xu (International Journal of Environmental Science and Technology, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

FMOD Alleviates Depression-Like Behaviors by Targeting the PI3K/AKT/mTOR Signaling After Traumatic Brain Injury - Xuekang Huang; Ziyu Zhu; Mengran Du; Chenrui Wu; Jiayuanyuan Fu; Jie Zhang; Weilin Tan; Biying Wu; Lian Liu; Z. B. Liao (NeuroMolecular Medicine, 2024)
Depression frequently occurs following traumatic brain injury (TBI). However, the role of Fibromodulin (FMOD) in TBI-related depression is not yet clear. Previous studies have suggested FMOD as a potential key factor in TBI, yet its association with depression post-TBI and underlying mechanisms are not well understood. Serum levels of FMOD were measured in patients with traumatic brain injury using qPCR. The severity of depression was assessed using the self-depression scale (SDS). Neurological function, depressive state, and cognitive function in mice were assessed using the modified Neurological Severity Score (mNSS), forced swimming test (FST), tail suspension test (TST), Sucrose Preference Test (SPT), and morris water maze (MWM). The morphological features of mouse hippocampal synapses and neuronal dendritic spines were revealed through immunofluorescence, transmission electron microscopy, and Golgi-Cox staining. The protein expression levels of FMOD, MAP2, SYP, and PSD95, as well as the phosphorylation levels of the PI3K/AKT/mTOR signaling pathway, were detected through Western blotting. FMOD levels were decreased in TBI patients’ serum. Overexpression of FMOD preserved neuronal function and alleviated depression-like behaviour, increased synaptic protein expression, and induced ultrastructural changes in hippocampal neurons. The increased phosphorylation of PI3K, AKT, and mTOR suggested the involvement of the PI3K/AKT/mTOR signaling pathway in FMOD’s protective effects. FMOD exhibits potential as a therapeutic target for depression related to TBI, with its protective effects potentially mediated through the PI3K/AKT/mTOR signaling pathway.

CFD- and BPNN- based investigation and prediction of air pollutant dispersion in urban environment - Xisheng Lin; Yunfei Fu; Daniel Z. Peng; Chun-Ho Liu; Mengyuan Chu; Zengshun Chen; Fan Yang; Tim K.T. Tse; Cruz Y. Li; Xinxin Feng (Sustainable Cities and Society, 2024)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

The dynamics of bubble breakup in heart-shaped microchannels: Effect of structure - Wanyuan He; Chunying Zhu; Taotao Fu; Xiqun Gao; Youguang Ma; Huai Z. Li (Chemical Engineering Journal, 2023)

Factors influencing the transfer and abundance of antibiotic resistance genes in livestock environments in China - Z. F. Wang; H. Yun; S. Li; J. Ji; A. Khan; X. L. Fu; P. Zhang; X. K. Li (International Journal of Environmental Science and Technology, 2023)

Regulation of autophagy of the heart in ischemia and reperfusion - Sergey V. Popov; Alexander V. Mukhomedzyanov; Nikita S. Voronkov; Ivan A. Derkachev; Alla A. Boshchenko; Feng Fu; Galina Z. Sufianova; Maria S. Khlestkina; Leonid N. Maslov (Apoptosis, 2023)

Cycle Length Evaluation in Persistent Atrial Fibrillation Using Kernel Density Estimation to Identify Transient and Stable Rapid Atrial Activity - Szabolcs Z. Nagy; Patrick Kasi; Valtino X. Afonso; Nathaniel Bird; Brian Pederson; Ian E. Mann; Steven Kim; Nicholas W. F. Linton; David C. Lefroy; Zachary I. Whinnett; Fu Siong Ng; Michael Koa-Wing; et al. (Cardiovascular Engineering and Technology, 2022)
Purpose Left atrial (LA) rapid AF activity has been shown to co-localise with areas of successful atrial fibrillation termination by catheter ablation. We describe a technique that identifies rapid and regular activity. Methods Eight-second AF electrograms were recorded from LA regions during ablation for psAF. Local activation was annotated manually on bipolar signals and where these were of poor quality, we inspected unipolar signals. Dominant cycle length (DCL) was calculated from annotation pairs representing a single activation interval, using a probability density function (PDF) with kernel density estimation. Cumulative annotation duration compared to total segment length defined electrogram quality. DCL results were compared to dominant frequency (DF) and averaging. Results In total 507 8 s AF segments were analysed from 7 patients. Spearman’s correlation coefficient was 0.758 between independent annotators ( P < 0.001), 0.837–0.94 between 8 s and ≥ 4 s segments ( P < 0.001), 0.541 between DCL and DF ( P < 0.001), and 0.79 between DCL and averaging ( P < 0.001). Poorer segment organization gave greater errors between DCL and DF. Conclusion DCL identifies rapid atrial activity that may represent psAF drivers. This study uses DCL as a tool to evaluate the dynamic, patient specific properties of psAF by identifying rapid and regular activity. If automated, this technique could rapidly identify areas for ablation in psAF.

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Sequence stratigraphy and Quaternary depositional systems in the Sanhu area of the Qaidam Basin, northwest China - Z. Liu; S. Fu; H. C. Jia; J. X. Tian; Y. H. Chen; C. Y. Dong (Australian Journal of Earth Sciences, 2019)

Epigenetic Alterations of Wnt Signaling Pathways in Nasopharyngeal Carcinoma - Pengfei Liu; Lu Fu; Robert Z. Qi (Current Pharmacology Reports, 2018)

Sequence subdivision and development characteristics of low-accommodation non-marine basins: a case study of the Yanchang Formation in the Ordos Basin - S. Fu; Z. Liu; Y.-Z. Li; Y.-R. Guo; X.-M. Xu; J.-J. Liu; X. D. Hu (Australian Journal of Earth Sciences, 2018)

Isometric strength of the hip abductors and external rotators in athletes with and without patellar tendinopathy - Z. J. Zhang; W. C. Lee; G. Y. F. Ng; S. N. Fu (European Journal of Applied Physiology, 2018)

DNA Barcoding for Identification of Sugarcane Borers in China - J- D Wang; W- Z Wang; Z- L Lin; A Ali; H- Y Fu; M- T Huang; S- J Gao; R Wang (Neotropical Entomology, 2018)

Alterations in mechanical properties of the patellar tendon is associated with pain in athletes with patellar tendinopathy - W. C. Lee; Z. J. Zhang; L. Masci; G. Y. F. Ng; Siu Ngor Fu (European Journal of Applied Physiology, 2017)

Parasitism Performance of Tetrastichus brontispae Ferriere over the Coconut Hispine Beetle, Brontispa longissima (Gestro) - K Liu; B L Fu; J R Lin; Y G Fu; Z Q Peng; Q A Jin; L D Tang (Neotropical Entomology, 2016)

Poisonings Associated with Intubation: US National Poison Data System Exposures 2000–2013 - G. A. Beauchamp; S. L. Giffin; B. Z. Horowitz; A. L. Laurie; R. Fu; R. G. Hendrickson (Journal of Medical Toxicology, 2016)

Effects of habitual loading on patellar tendon mechanical and morphological properties in basketball and volleyball players - Z. J. Zhang; G. Y. F. Ng; S. N. Fu (European Journal of Applied Physiology, 2015)

Effect of Biochar in Cadmium Availability and Soil Biological Activity in an Anthrosol Following Acid Rain Deposition and Aging - H. Lu; Z. Li; S. Fu; A. Méndez; G. Gascó; J. Paz-Ferreiro (Water, Air, & Soil Pollution, 2015)

Identification of the trehalose-6-phosphate synthase gene family in winter wheat and expression analysis under conditions of freezing stress - D. W. XIE; X. N. WANG; L. S. FU; J. SUN; W. ZHENG; Z. F. LI (Journal of Genetics, 2015)

Effects of fasting and feeding on the fast‐start swimming performance of southern catfish Silurus meridionalis - G. J. Yan; X. K. He; Z. D. Cao; S. J. Fu (Journal of Fish Biology, 2015)
This study investigated the effects of fasting and feeding on the fast‐start escape swimming performance of juvenile southern catfish Silurus meridionalis , a sit‐and‐wait forager that encounters extreme fasting and famine frequently during its lifespan. Ten to 30 days of fasting resulted in no significant change in most of the variables measured in the fast‐start response except a 20–30% decrease in the escape distance during the first 120 ms ( D 120ms ) relative to the control group (48 h after feeding). The ratio of the single‐bend ( SB ) response (lower energetic expenditure) to the double‐bend ( DB ) response increased significantly from 0% in the control group to 75 and 82·5% in the 20 and 30 day fasting groups, respectively. Satiated feeding (25% of body mass) resulted in a significantly lower (36·6%) maximum linear velocity ( V max ) and a significantly lower (43·3%) D 120ms than in non‐fed fish (control group, 48 h after feeding). Half‐satiated feeding (12·5% of body mass), however, showed no significant effects on any of the measured variables of the fast‐start response relative to control fish. It is suggested that the increase in the ratio of SB : DB responses with fasting in S. meridionalis may reflect a trade‐off between energy conservation and maintaining high V max , while variables of fast‐start performance were more sensitive to feeding than fasting might be an adaptive strategy to their foraging mode and food availability in their habitat.

A novel fish cell line derived from the brain of Chinese perch Siniperca chuatsi : development and characterization - X. Fu; N. Li; Y. Lai; X. Luo; Y. Wang; C. Shi; Z. Huang; S. Wu; J. Su (Journal of Fish Biology, 2015)
In this study, a continuous cell line (named as CPB ) was established from Siniperca chuatsi brain and has been subcultured >140 times. CPB cell line predominantly consisted of fibroblast‐like cells that could grow better in Leibovitz's L‐15 supplemented with 10% foetal bovine serum at 28° C. Polymerase chain reaction amplification of 18s recombinant (r)RNA confirmed the origin of this cell line from S. chuatsi . The CPB cell line was cryopreserved at different passage levels and revived successfully with 80–90% survival. The cell line was further characterized by chromosome number and transfection. The CPB cells were highly susceptible to infectious spleen and kidney necrosis virus ( ISKNV ) with a titre of 6·58–6·62 log TCID 50 ml −1 and numerous ISKNV particles were observed in the cytoplasm by transmission electron microscopy. At the same time, ISKNV infection was confirmed by reverse transcriptase polymerase chain reaction, immunodot blot and individual challenge experiments. The development and characterization of a new brain cell line from S. chuatsi were described in this study and it could be used as an in vitro tool for propagation of ISKNV and gene expression studies.

Effect of the invasive bivalve Mytilopsis sallei on the macrofaunal fouling community and the environment of Yundang Lagoon, Xiamen, China - L.-Z. Cai; J.-S. Hwang; H.-U. Dahms; S.-J. Fu; Y. Zhuo; T. Guo (Hydrobiologia, 2014)

Quantitative trait analysis of flowering time in spring rapeseed (B. napus L.) - Y. X. Luo; C. Y. Luo; D. Z. Du; Z. Fu; Y. M. Yao; C. C. Xu; H. S. Zhang (Euphytica, 2014)

Prevalence of carbapenem-hydrolyzing class D β-lactamase genes in Acinetobacter spp. isolates in China - S. Ji; Y. Chen; Z. Ruan; Y. Fu; J. Ji; Y. Fu; H. Wang; Y. Yu (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

A Factorial-based Dynamic Analysis Method for Reservoir Operation Under Fuzzy-stochastic Uncertainties - D. Z. Fu; Y. P. Li; G. H. Huang (Water Resources Management, 2013)

Scl gene construction, expression and effect on hemangioma - H. X. Yin; Z. H. Zhang; J. C. Shen; A. L. Zhang; T. Y. Zhang; J. X. Luo; C. Y. Fu; X. P. Yi; Z. W. Liu; S. S. Yang; B. Zhou; X. Fu (Molecular Biology Reports, 2013)

Characterization and expression of Cd8 molecules in mandarin fish Siniperca chuatsi - Z. Guo; G. L. Wang; J. P. Fu; P. Nie (Journal of Fish Biology, 2013)
The full‐length complementary DNA (cDNA) sequences encoding cd8α and cd8β molecules were sequenced and characterized from mandarin fish Siniperca chuatsi . Conserved motifs and residues were found to be present in derived peptides of the Cd8 molecules. For example, WXR motif, DXGXYXC motif, and four cysteine residues were present in the extracellular region of the Cd8 protein. Threonine, serine and proline residues involved in multiple O ‐linked glycosylation events were located in the membrane proximal hinge region. The common CPH motif in the cytoplasmic tail was detected similar to other teleost Cd8 molecules. Different from those in mammals, S. chuatsi Cd8 sequences have many extra cysteine residues (C149 in Cd8 α sequence and C46, C51 and C158 in Cd8 β sequence), which also exist in other teleost Cd8 molecules. Real‐time polymerase chain reaction (RT‐PCR) and Western blot analyses revealed that the thymus had the highest expression of cd8 messenger (m)RNA and protein. After stimulated with phytohaemagglutinin, polyriboinsine‐polyribocyaidylic acid and concanavalin A (ConA), the expression level of cd8 mRNA increased significantly in head‐kidney lymphocytes at 4 and 8 h, but decreased to normal level at 12 h. Similarly, stimulation with ConA in vivo also led to an increase in the cd8 mRNA level in the spleen. Immunohistochemistry analysis demonstrated that Cd8 α ‐positive cells can be detected in the thymus, spleen and intestine by using polyclonal anti‐Cd8 α antibody.

Arsenic accumulation and distribution in the tissues of inbred lines in maize (Zea mays L.) - Z. H. Liu; W. H. Li; H. Y. Qi; G. L. Song; D. Ding; Z. Y. Fu; J. B. Liu; J. H. Tang (Genetic Resources and Crop Evolution, 2012)

Microbiologic characteristics of pathogenic bacteria from hospitalized trauma patients who survived Wenchuan earthquake - B. Zhang; Z. Liu; Z. Lin; X. Zhang; W. Fu (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Constitutive expression of barley α-amylase in Pichia pastoris by high-density cell culture - Z. W. Liu; H. X. Yin; X. P. Yi; A. L. Zhang; J. X. Luo; T. Y. Zhang; C. Y. Fu; Z. H. Zhang; J. C. Shen; L. P. Chen (Molecular Biology Reports, 2012)

A fuzzy-Markov-chain-based analysis method for reservoir operation - D. Z. Fu; Y. P. Li; G. H. Huang (Stochastic Environmental Research and Risk Assessment, 2012)

Genomic sequence of an avian paramyxovirus type 1 strain isolated from Muscovy duck (Cairina moschata) in China - S.-H. Shi; Yu Huang; S.-J. Cui; L.-F. Cheng; G.-H. Fu; X. Li; Z. Chen; C.-X. Peng; F. Lin; J.-S. Lin; Jing-Liang Su (Archives of Virology, 2011)

A new long terminal repeat (LTR) sequence allows to identify J genome from JS and St genomes of Thinopyrum intermedium - Z. X. Tang; Z. J. Yang; S. L. Fu; M. Y. Yang; G. R. Li; H. Q. Zhang; F. Q. Tan; Zhenglong Ren (Journal of Applied Genetics, 2011)

Differential expression of microRNA-1 in dorsal root ganglion neurons - Isabell Bastian; Sunil Tam Tam; Xin-Fu Zhou; Jan Kazenwadel; Mark Hoek; Michael Z. Michael; Ian Gibbins; Rainer Viktor Haberberger (Histochemistry and Cell Biology, 2011)

Molecular characterization and association analysis of FBXO40 with partial hematological indexes in pig - Z. W. Wang; X. Y. Li; Z. L. Tang; S. L. Yang; Z. Z. Ying; T. Fu; B. Fan; Y. L. Mu; H. Ao; K. Li (Molecular Biology Reports, 2010)

QTL detection for grain oil and starch content and their associations in two connected F2:3 populations in high-oil maize - Y. Z. Wang; J. Z. Li; Y. L. Li; M. G. Wei; X. H. Li; J. F. Fu (Euphytica, 2010)

Transfer to wheat (Triticum aestivum) of small chromosome segments from rye (Secale cereale) carrying disease resistance genes - S. Fu; Z. Tang; Z. Ren; H. Zhang (Journal of Applied Genetics, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

Vertical Distribution of Polybrominated Diphenyl Ethers (PBDEs) in Soil Cores Taken from a Typical Electronic Waste Polluted Area in South China - Z. Z. Yang; Y. F. Li; Y. X. Hou; H. Y. Liang; Z. F. Qin; S. Fu (Bulletin of Environmental Contamination and Toxicology, 2010)

Tissue Distribution of Polybrominated Diphenyl Ethers (PBDEs) in Captive Domestic Pigs, Sus scrofa, from a Village Near an Electronic Waste Recycling Site in South China - Y. F. Li; Z. Z. Yang; C. H. Wang; Z. J. Yang; Z. F. Qin; S. Fu (Bulletin of Environmental Contamination and Toxicology, 2010)

Co-location of seed oil content, seed hull content and seed coat color QTL in three different environments in Brassica napus L. - X. Y. Yan; J. N. Li; F. Y. Fu; M. Y. Jin; L. Chen; L. Z. Liu (Euphytica, 2009)

Polybrominated Diphenyl Ethers in the Soil of Typical Industrial City - K. Li; S. Fu; Z. Z. Yang; X. B. Xu (Bulletin of Environmental Contamination and Toxicology, 2009)

Dent corn genetic background influences QTL detection for grain yield and yield components in high-oil maize - Y. L. Li; X. H. Li; J. Z. Li; J. F. Fu; Y. Z. Wang; M. G. Wei (Euphytica, 2009)

Composition, Distribution, and Characterization of Polybrominated Diphenyl Ethers in Sandstorm Depositions in Beijing, China - S. Fu; Z. Z. Yang; L. Zhang; K. Li; X. B. Xu (Bulletin of Environmental Contamination and Toxicology, 2009)

Polybrominated Diphenyl Ethers in Mudsnails (Cipangopaludina cahayensis) and Sediments from an Electronic Waste Recycling Region in South China - Z. Z. Yang; X. R. Zhao; Z. F. Qin; S. Fu; X. H. Li; X. F. Qin; X. B. Xu; Z. X. Jin (Bulletin of Environmental Contamination and Toxicology, 2009)

Reduced swimming abilities in fast‐growing transgenic common carp Cyprinus carpio associated with their morphological variations - D. Li; W. Hu; Y. Wang; Z. Zhu; C. Fu (Journal of Fish Biology, 2009)
Critical swimming speeds ( U crit ) and morphological characters were compared between the F 4 generation of GH‐transgenic common carp Cyprinus carpio and the non‐transgenic controls. Transgenic fish displayed a mean absolute U crit value 22·3% lower than the controls. Principal component analysis identified variations in body shape, with transgenic fish having significantly deeper head, longer caudal length of the dorsal region, longer standard length ( L S ) and shallower body and caudal region, and shorter caudal length of the ventral region. Swimming speeds were related to the combination of deeper body and caudal region, longer caudal length of the ventral region, shallower head depth, shorter caudal length of dorsal region and L S . These findings suggest that morphological variations which are poorly suited to produce maximum thrust and minimum drag in GH‐transgenic C. carpio may be responsible for their lower swimming abilities in comparison with non‐transgenic controls.

Composition, Distribution and Characterization of Polybrominated Diphenyl Ethers (PBDEs) in the Soil in Taiyuan, China - K. Li; S. Fu; Z. Z. Yang; X. B. Xu (Bulletin of Environmental Contamination and Toxicology, 2008)

Polychlorinated Biphenyls Residues in the Soil in Linfen, China - S. Fu; H. Cheng; Y. Liu; L. Zhang; Z. Yang; K. Li; X. Xia; X. Xu (Bulletin of Environmental Contamination and Toxicology, 2008)

Composition, Distribution, and Characterization of Organochlorine Pesticides in Sandstorm Depositions in Beijing, China - S. Fu; K. Li; Z. Z. Yang; X. B. Xu (Water, Air, & Soil Pollution, 2008)

Production of a new wheat cultivar with a different 1B.1R translocation with resistance to powdery mildew and stripe rust - Z. Tang; S. Fu; Z. Ren; H. Zhang; Z. Yang; B. Yan; H. Zhang (Cereal Research Communications, 2008)

Simulation of direct effects of black carbon aerosol on temperature and hydrological cycle in Asia by a Regional Climate Model - J. Wu; C. Fu; Y. Xu; J. P. Tang; W. Wang; Z. Wang (Meteorology and Atmospheric Physics, 2008)

Contamination Status of Hexachlorobenzene (HCB) in Sandstorm Depositions from Beijing and the Origination Region - S. Fu; K. Li; Z. Yang; X. B. Xu (Bulletin of Environmental Contamination and Toxicology, 2008)

Is peak postprandial oxygen consumption positively related to growth rate and resting oxygen consumption in a sedentary catfish Silurus meridionalis ? - S. J. Fu; Z. D. Cao; J. L. Peng; Y. X. Wang (Journal of Fish Biology, 2008)
The resting oxygen consumption , postprandial and post‐exercise peak oxygen consumption of 137 juvenile southern catfish Silurus meridionalis , weighing 18·5 ± 0·8 g (mean ± s . d .), were measured at 25° C to determine whether is positively related to postprandial and post‐exercise in sedentary S. meridionalis . In addition, postprandial metabolic response [ i.e. the specific dynamic action (SDA)] after a satiating meal and the growth performance as a consequence of a 3 week feeding‐growth trail were measured in 40 S. meridionalis , weighing 14·3 ± 0·2 g, at 25° C to determine whether postprandial is positively related to growth rate. Postprandial was positively correlated with , while post‐exercise was not. Both postprandial and post‐exercise were positively correlated with factorial and absolute scope. There was no significant correlation between the growth rate and postprandial in S. meridionalis . It suggested that as a sit‐and‐wait forager with low , low post‐exercise and high postprandial , the expenditure of energy for maintenance in S. meridionalis may be more closely related to digestive processes than locomotor activities.

Radiation-Guided P-Selectin Antibody Targeted to Lung Cancer - G. Hariri; Y. Zhang; A. Fu; Z. Han; M. Brechbiel; M. N. Tantawy; T. E. Peterson; R. Mernaugh; D. Hallahan (Annals of Biomedical Engineering, 2008)

Fast‐growing transgenic common carp mounting compensatory growth - C. Fu; D. Li; W. Hu; Y. Wang; Z. Zhu (Journal of Fish Biology, 2007)
Compensatory growth is a phase of accelerated growth apparent when favourable conditions are restored after a period of growth depression. To investigate if F 2 common ‘all‐fish’ growth hormone gene transgenic common carp ( Cyprinus carpio ) could mount compensatory growth, a 9 week study at 29° C was performed. The control group was fed to satiation twice a day throughout the experiment. The other two groups were deprived of feed for 1 or 2 weeks, respectively, and then fed to satiation during the re‐feeding period. At the end of the experiment, the live masses of fish in the deprived groups were still significantly lower than those of the controls. During the re‐feeding period, size‐adjusted mean specific growth rates and mean feed intakes were significantly higher in the deprived fish than in the controls, indicating a partial compensatory growth response in these fish. No significant differences were found in food conversion efficiency between the deprived and control fish during re‐feeding, suggesting that hyperphagia was the mechanism responsible for increased growth rates. The proximate composition of the deprived fish at the end of the experiment was similar to that of the control fish. This study is, to our knowledge, the first to report that fast‐growing transgenic fish can achieve partial compensation of growth following starvation.

Two new flavanes and bioactive compounds from Daphne tangutica Maxim - W. Zhang; Y. H. Shen; Z. Y. Lou; R. H. Liu; C. Zhang; P. Fu; L. Shan; W. D. Zhang (Natural Product Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Composition and antimicrobial activity of the essential oil of Actinidia macrosperma from China - Y. Lu†; Y. P. Zhao†; Z. C. Wang; S. Y. Chen; C. X. Fu* (Natural Product Research, 2007)

Sesquiterpene lactones from Saussurea alata - G. Ren; Z. M. Yu; Y. L. Chen; S. H. Wu; C. X. Fu (Natural Product Research, 2007)

Growth and energy budget of F 2 ‘all‐fish’ growth hormone gene transgenic common carp - C. Fu; D. Li; W. Hu; Y. Wang; Z. Zhu (Journal of Fish Biology, 2007)
The growth and energy budget for F 2 ‘all‐fish’ growth hormone gene transgenic common carp Cyprinus carpio of two body sizes were investigated at 29·2° C for 21 days. Specific growth rate, feed intake, feed efficiency, digestibility coefficients of dry matter and protein, gross energy intake ( I E ), and the proportion of I E utilized for heat production ( H E ) were significantly higher in the transgenics than in the controls. The proportion of I E directed to waste products [faecal energy ( F E ) and excretory energy loss ( Z E + U E ) where Z E is through the gills and U E through the kidney], and the proportion of metabolizable energy ( M E ) for recovered energy ( R E ) were significantly lower in the transgenics than in the controls. The average energy budget equation of transgenic fish was as follows: 100 I E = 19·3 F E + 6·0 ( Z E + U E ) + 45·2 H E + 29·5 R E or 100 M E = 60·5 H E + 39·5 R E . The average energy budget equation of the controls was: 100 I E = 25·2 F E + 7·4 ( Z E + U E ) + 35·5 H E + 31·9 R E or 100 M E = 52·7 H E + 47·3 R E . These findings indicate that the high growth rate of ‘all‐fish’ transgenic common carp relative to their non‐transgenic counterparts was due to their increased feed intake, reduced lose of waste productions and improved feed efficiency. The benefit of the increased energy intake by transgenic fish, however, was diminished by their increased metabolism.

Two new xanthones from Hypericum japonicum - P. Fu; W.-D. Zhang; R. H. Liu; T.-Z. Li; Y.-H. Shen; H.-L. Li; W. Zhang; H.-S. Chen (Natural Product Research, 2006)

Geochemical evidence for the variation of historical seabird population on Dongdao Island of the South China Sea - X. D. Liu; S. P. Zhao; L. G. Sun; H. H. Luo; X. B. Yin; Z. Q. Xie; Y. H. Wang; K. X. Liu; X. H. Wu; X. F. Ding; D. P. Fu (Journal of Paleolimnology, 2006)

Genetic analyses and mapping of a new thermo-sensitive genic male sterile gene in maize - J. H. Tang; Z. Y. Fu; Y. M. Hu; J. S. Li; L. L. Sun; H. Q. Ji (Theoretical and Applied Genetics, 2006)

Complete nucleotide sequences and genome characterization of double-stranded RNA 1 and RNA 2 in the Raphanus sativus-root cv. Yipinghong - L. Chen; J. S. Chen; L. Liu; X. Yu; S. Yu; T. Z. Fu; W. H. Liu (Archives of Virology, 2006)

QTLs for drought escape and tolerance identified in a set of random introgression lines of rice - J. L. Xu; H. R. Lafitte; Y. M. Gao; B. Y. Fu; R. Torres; Z. K. Li (Theoretical and Applied Genetics, 2005)

Effect of feeding level and feeding frequency on specific dynamic action in Silurus meridionalis - S. J. Fu; X. J. Xie; Z. D. Cao (Journal of Fish Biology, 2005)
The effect of feeding level ( F L ; 0·5 to 4% dry diet mass per wet fish body mass) and feeding frequency (once every 4 days to twice per day) on postprandial metabolic response was investigated in southern catfish Silurus meridionalis at 27·5° C. The results showed that there was no significant difference in the specific dynamic action (SDA) coefficient among the groups of different feeding levels ( P > 0·05). The duration increased from 26·0 to 40·0 h and the peak metabolic rate increased from 207·8 to 378·8 mg O 2 kg −1 h −1 when the feeding level was increased from 0·5 to 4%. The relationship between the peak metabolic rate ( R P , mg O 2 kg −1 h −1 ) and F L could be described as: R P = 175·4 + 47·3 F L ( r 2 = 0·943, n = 40, P D , h) and F L could be described as D =30·97 F L 0·248 ( r 2 =0·729, n =40, P

Effect of fasting on resting metabolic rate and postprandial metabolic response in Silurus meridionalis - S. J. Fu; X. J. Xie; Z. D. Cao (Journal of Fish Biology, 2005)
Resting metabolic rate in southern catfish of 2 and 5 day fasting groups were significantly higher than that of the 15 day fasting group ( P P P P

Simulation Studies of High-Latitude Magnetospheric Boundary Dynamics - Q. Q. Shi; Z. Y. Pu; H. Zhang; S. Y. Fu; C. J. Xiao; Q. -G. Zong; T. A. Fritz; Z. X. Liu (Surveys in Geophysics, 2005)

Energetic Particles Observed in the CUSP Region During a Storm Recovery Phase - S. Y. Fu; Q. G. Zong; Z. Y. Pu; C. J. Xiao; A. Korth; P. Daly; H. Reme (Surveys in Geophysics, 2005)

Multiple Flux Rope Events at the High-Latitude Magnetopause: Cluster/Rapid Observation on 26 January, 2001 - Z. Y. Pu; Q. -G. Zong; T. A. Fritz; C. J. Xiao; Z. Y. Huang; S. Y. Fu; Q. Q. Shi; M. W. Dunlop; K. -H. Glassmeier; A. Balogh; P. Daly; H. Reme; et al. (Surveys in Geophysics, 2005)

Molecular diversity and multilocus organization of the parental lines used in the International Rice Molecular Breeding Program - S. B. Yu; W. J. Xu; C. H. M. Vijayakumar; J. Ali; B. Y. Fu; J. L. Xu; Y. Z. Jiang; R. Marghirang; J. Domingo; C. Aquino; S. S. Virmani; Z. K. Li (Theoretical and Applied Genetics, 2003)

Suppression of multipath and jamming signals by digital beamforming for GPS/Galileo applications - Z. Fu; A. Hornbostel; J. Hammesfahr; A. Konovaltsev (GPS Solutions, 2003)

The distributions and effects of nutrients in the sediments of a shallow eutrophic Chinese lake - Fu-Liu Xu; S. Tao; R. W. Dawson; Z. R. Xu (Hydrobiologia, 2003)

Attenuated Lapinized Chinese Strain of Classical Swine Fever Virus: Complete Nucleotide Sequence and Character of 3′-Noncoding Region - H. X. Wu; J. F. Wang; C. Y. Zhang; L. Z. Fu; Z. S. Pan; N. Wang; P. W. Zhang; W. G. Zhao (Virus Genes, 2001)

Relative Lymphocytosis-Disorder Caused by Occupational Exposure to Vinyl Chloride Monomer - A. Fu ) i '; Z. x pacir; D. Barkovi '; A. Jazbec; A. Miji '; B. Labar (Bulletin of Environmental Contamination and Toxicology, 1998)

Growth and feed utilization by F 4 human growth hormone transgenic carp fed diets with different protein levels - C. Fu; Y. Cui; S. S. O. Hung; Z. Zhu (Journal of Fish Biology, 1998)
The F 4 generation of human growth hormone (hGH) transgenic red common carp Cyprinus carpio had significantly higher growth rates than the non‐transgenic controls. Protein and energy intakes were significantly higher in the transgenic carp than in the controls fed the 20% protein diet, but were not different between the two strains fed diets with 30 and 40% protein. Faecal protein loss, as a proportion of protein intake, was significantly lower in the transgenics than in the controls fed diets with 20 and 30% protein, but was not different between the two strains fed diet with 40% protein. Faecal energy loss, as a proportion of energy intake, was significantly lower in the transgenics than in the controls fed diet with 20% protein, but was not different between the two strains fed diets with 30 and 40% protein. Recovered protein, as a proportion of protein intake, was significantly higher in the transgenics than in the controls fed all diets, whereas recovered energy was significantly higher in the transgenic fish fed the 40% protein diet. For fish fed each diet, the transgenics had significantly higher body contents of dry matter and protein, but lower contents of lipid than the controls. It was concluded that transgenics were more efficient in utilizing dietary protein than the controls. At a lower dietary protein level, transgenics achieved higher growth rates mainly by increasing feed intake; at higher levels of dietary protein, transgenics achieved higher growth rates mainly through a higher energy conversion efficiency.

Comparative Analyses of Soil Contaminant Levels and Plant Species Diversity at Developing and Disused Oil Well Sites in Qianjiang Oilfield, China - Z.-T. Xiong; H.-X. Hu; Y.-X. Wang; G.-H. Fu; Z.-Q. Tan; G.-A. Yan (Bulletin of Environmental Contamination and Toxicology, 1997)

A one-year survey of rotavirus strains from three locations in Bangladesh - Leanne E. Unicomb; Fu Bingnan; Z. Rahim; N. N. Banu; J. G. Gomes; G. Podder; M. H. Munshi; S. R. Tzipori (Archives of Virology, 1993)